2014
DOI: 10.5812/jjm.12776
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Exposure and the Risk of Schizophrenia

Abstract: Background:Schizophrenia is a major psychiatric disorder with a deeply destructive pathophysiology. There are evidences to indicate that infectious agents such as Toxoplasma gondii may play some roles in etiology of the disorder.Objectives:The current study aimed to determine the association between T. gondii exposure and the risk of schizophrenia.Materials and Methods:T. gondii IgG antibodies of 100 patients with schizophrenia as well as 200 healthy volunteers were assessed. The subjects also completed demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
(34 reference statements)
1
15
0
2
Order By: Relevance
“…According to these findings, residential area has no effect on the risk of toxoplasmosis. In line with our results, Khademvatan et al (2014) and Xiao et al (2010) found that individuals living in urban and rural areas in Iran did not have significantly different seroprevalence of T. gondii infection (35,41). In contrast, Yuksel et al and Kolbekova et al reported a significant correlation between residences in a small town/village and toxoplasmosis (42,43).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…According to these findings, residential area has no effect on the risk of toxoplasmosis. In line with our results, Khademvatan et al (2014) and Xiao et al (2010) found that individuals living in urban and rural areas in Iran did not have significantly different seroprevalence of T. gondii infection (35,41). In contrast, Yuksel et al and Kolbekova et al reported a significant correlation between residences in a small town/village and toxoplasmosis (42,43).…”
Section: Discussionsupporting
confidence: 71%
“…Khademvatan et al (2014) also showed that the seroprevalence of anti-T. gondii IgG antibodies in schizophrenia patients and healthy volunteers in Ahvaz, Iran, was 34% and 26.5%, respectively (35). Hamidinejat et al (2012) also demonstrated that the positivity rate of anti-T. gondii IgG antibodies among individuals with schizophrenia (57.1%) was significantly higher than healthy controls (29.2%) (36).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Out of the 2,604 different articles in English, French, Spanish, Portuguese, Chinese, and Russian, initially identified for co-morbidities between mental health and chronic physical diseases, and for comorbidities between mental health and neurotropic parasitic diseases, 18 articles were included in our meta-analysis ( Figure 1). Among these 18 articles of co-morbidity studies on mental disorders and neurotropic parasitic diseases [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] published between 1997 and 2016 and meeting our inclusion criteria, two were prevalence studies in individuals with neurotropic parasitic diseases who were screened for mental disorders, and sixteen were analytical studies in individuals with mental disorders who were screened for neurotropic parasitic diseases (Table 2 and Table 3).…”
Section: General Resultsmentioning
confidence: 99%
“…Based on recent studies, chronic toxoplasmosis may associated with autoimmune and neurodegenerative disorders [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%